High Level Discourse in the ELA Classroom: Analyzing and Assessing Author’s Purpose (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
The aims of this manuscript are to analyze the definitions and practices of discourse as they exist in English language arts classrooms currently and to identify why sophisticated discourse is a necessary tool in assessments. Sophisticated discourse is the most efficient and impactful method for ELA educators to assess the ways in which their students are understanding author’s purpose in complex pieces of literature. Sophisticated discourse is inclusive and does not discount any persons’ ideas surrounding the text. It allows for educators to evaluate all students’ understanding of complex ideas in a text more efficiently, and it prepares and encourages students to think more deeply about the literature and how to apply it to real life scenarios.  Keywords: sophisticated discourse, author’s purpose, literature
Keywords: discourse